Sucesión por causa de muerte, vivienda, migración y familia en el Derecho cubano: Un atinado giro copernicano - Pérez Gallardo, Leonardo B. (Revista de Derecho, 2019)
In the last two years the foundations of Cuban civil and real estate legislation have moved, with special emphasis in what regards to the transmission of estate, whether because of inter vivos or mortis causa acts. In this last order, the change brought about favors heirs, in correspondence with the constitutional tutelage which the right to inheritance has in Cuba. In such way, the exaggerated tuition of cohabitants has been left behind opening the door to a Law which accommodates to the compasses of the succession norms regulated by the Civil Code.